Tathwir Namudhaj at-Ta'lim al-Mudmaj li Tanmiyat Maharat al-Fahm al-Qira'i fi Qism al-Adab al-'Arabi bi Jami'at Malang al-Hukumiyah - Dariyadi, Moch. Wahib (Universitas Negeri Malang, 2024)
The Department of Arabic Literature at Malang State University faces a problem of weak reading comprehension among students in the extensive reading course, with an average score of 77.18. This issue is attributed to the educational materials not being designed to meet the students' needs and the ineffective use of technology. This research aims to develop a blended learning model to improve students' reading comprehension, focusing on: (1) producing an Arabic language teaching model based on blended learning in the extensive reading course, (2) assessing the validity of the developed model, and (3) measuring the effectiveness of the model's application in improving academic achievement. The study used the development method by modifying the Borg and Gall model, and data were collected through interviews, observations, questionnaires, and tests, analyzed both qualitatively descriptively and statistically. The results showed: (1) the production of an Arabic language teaching program based on blended learning that includes an electronic learning management system and a discussion forum, (2) the developed model is valid for use according to experts' opinions, and (3) the developed model is effective in improving students' academic achievement based on a paired T-test with a probability value of 0.000 and a calculated T value of -23.869, indicating statistically significant differences in academic achievement after the model's application. This research presented an educational model for reading comprehension skills in the extensive reading course at the university level, with the integration of technology into the teaching process to meet the needs of students in learning the Arabic language, which opens up new information to develop their language skills. تواجه قسم الأدب العربي بجامعة مالانج الحكومية مشكلة في ضعف مهارة الفهم القرائي في مادة القراءة الموسعة، بمتوسط درجة 77.18. ويعود ذلك إلى عدم تطوير المواد التعليمية بما يلبي احتياجات الطلبة وعدم الاستفادة من التكنولوجيا بشكل فعال في عملية التعليم. يهدف هذا البحث إلى تطوير نموذج التعليم المدمج لتحسين الفهم القرائي للطلبة، ويركز على: (1) إنتاج نموذج تعليم اللغة العربية القائم على التعليم المدمج في مادة القراءة الموسعة، (2) قياس صلاحية النموذج المطور، و (3) قياس فعالية تطبيق النموذج المطور لتحسين التحصيل الدراسي. استخدم الباحث هذه الدراسة منهج التطوير بتعديل من نموذج بروج وغال، وتم جمع البيانات من خلال المقابلات والملاحظات والاستبانات والاختبارات، وتحليلها وصفياً كيفياً وإحصائياً. أظهرت النتائج: (1) إنتاج برنامج تعليم اللغة العربية القائم على التعليم المدمج يتضمن نظام إدارة التعلم الإلكتروني ومنتدى النقاش، (2) النموذج المطور صالح للاستخدام حسب آراء الخبراء، و (3) النموذج المطور فعال في تحسين التحصيل الدراسي للطلبة بناءً على اختبار T المزدوج بمعامل احتمالية 0.000 وT المحسوب -23.869 مما يدل على وجود فروق دالة إحصائياً في التحصيل الدراسي بعد تطبيق النموذج. قدم هذا البحث نموذجا تعليميا لمهارة الفهم القرائي في مادة القراءة الموسعة في المستوى الجامعي، مع دمج التكنولوجيا في عملية التدريس لتلبية احتياجات الطلبة في تعليم اللغة العربية مما يفتح معلومات جديدة لتنمية مهاراتهم اللغوية.